Sensor and actuator stochastic modeling of the Lego mindstorms NXT educational kit - Gonçalves, José (2010)
This paper describes the sensor and actuator stochastic modeling of Lego Mindstorms NXT educational kit. It will be also presented the experimental setups applied to obtain each sensor and actuator parameters. The introduction of an industrial robot in some of the experimental setups allowed to increase the speed, repeatability and to reduce errors in the process of sensor data collecting.